The Role of Capital Structure in Moderating Profitability in Consumer Non-Cyclicals Companies for the Period 2021–2023 - Loman, Devina; Situmorang, Iskandar Muda; Mie, Mie (CV. Civiliza Publishing, 2025)
The objective of this study is to examine and analyze whether sales growth, corporate social responsibility, and accounts receivable turnover affect profitability, with capital structure as a moderating variable, in consumer non-cyclical companies listed on the Indonesia Stock Exchange for the period 2021–2023. This research is based on information obtained from the Indonesia Stock Exchange. The sampling technique used is purposive sampling. The population of this study consists of 126 consumer non-cyclical companies listed on the Indonesia Stock Exchange during the 2021–2023 period, with a final sample of 93 companies, resulting in a total of 279 observations. Hypothesis testing was conducted using panel data regression analysis with the E-Views 9 application. The results show that sales growth and accounts receivable turnover have a positive effect on profitability, while corporate social responsibility has no significant effect on profitability. Capital structure is found to moderate the effect of corporate social responsibility on profitability but does not moderate the effects of sales growth and accounts receivable turnover on profitability.